(NdRAMATURGIQ I TEATRALXNAQ KRITIKA (B/ s (N~ASTX (B4s - (NnEKRASOW(B, (NnIKOLAJ aLEKSEEWI^s ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1966)
(Nw ^ETWERTYJ TOM WO[LI DRAMATI^ESKIE PROIZWEDENIQ I TEATRALXNAQ KRITIKA (B1840-1867 (NGG(B.s
rus
Keywords: (NpXESYs; (NkRITIKAs